The role of Sophora alopecuroides alkaloids in colon health of lambs fed high-concentrate diets for extended periods: impact on barrier function, antioxidation, and microflora - Li, Shufang; Li, Boyang; Lu, Henan; Zhao, Jianxin; Gao, Aiwu; An, Yawen; Yang, Jinli; Wang, Hairong (Frontiers in Veterinary Science, 2025)
IntroductionLong-term feeding of a high-concentrate diet can induce subacute ruminal acidosis (SARA) and hindgut acidosis in ruminants. However, at present, most studies focus on reducing rumen injury by adjusting the feed formula, adding buffers, probiotics, or enzyme preparations, and few studies pay attention to hindgut health. Sophora alopecuroides alkaloids have extensive anti-inflammatory and antioxidant effects. The purpose of this experiment was to study the effects of adding total alkaloids of Sophora alopecuroides (TASA) to a high-concentrate diet on colon barrier function, antioxidation, and the microbial flora of lambs.Methods18 Dumont lambs (26.37 ± 2.29 kg) were divided into three diet groups: medium-concentrate diet (MC, concentrate ratio 50:50), high-concentrate diet (HC, concentrate ratio 70:30), and HC diet supplemented with 121 mg/kg TASA (HCT). At the end of the experimental period, colon contents and colon epithelium were collected. These samples were used to evaluate the colon barrier, antioxidant capacity, intestinal morphology, microbial composition and short-chain fatty acid (SCFA) concentration.ResultsThe results revealed that adding TASA to the HC diet increased claudin-1 protein expression (p < 0.01), decreased the MDA concentration, and increased Glutathione peroxidase (GSH-Px), Superoxide dismutase (SOD), and Total antioxidant capacity (T-AOC) activity in the colonic epithelium (p < 0.05). The concentration of propionate and lactate in colon contents in HC group increased significantly, while the pH decreased significantly (p < 0.05). The concentration of acetate, propionate and lactate in HCT group was significantly lower than that in HC group, the concentration of butyrate in HCT group was the highest (p < 0.05). Furthermore, there was a significant increase in Bacteroidetes and a decrease in Firmicutes in the HCT group (p < 0.01). Compared with the HC group, there was a notable increase in the butyrate-producing genera Faecalibacterium, Roseburia, Lachnospiraceae_NK4A136_group, and Butyrivibrio in the HCT group (p < 0.05 or p < 0.01). Additionally, the abundances of Prevotellaceae_UCG-003 in the MC and HCT groups were significantly greater (p < 0.05 or p < 0.01).ConclusionIn conclusion, supplementing the HC diet with TASA enhances colonic barrier and antioxidant functions, and alleviates HC diet-induced colonic damage by modulating the structure and abundance of the colonic microbiota.